Pengaruh Terapi Massage terhadap Nyeri pada Pasien Low Back Pain - Hasibuan, Desi Lianti Sari; Flora, Many; Tarigan, Mula (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Low Back Pain is a common problem caused because the lumbar region bears most of the weight. Pain and disability is one of the problems that can be caused by LBP which has an impact on life. Non-pharmacological interventions, such as massage, acupuncture, spinal manipulation, tai chi, and yoga, are recommended as first treatment preference for LBP. This systematic review aims to determine the benefits of massage therapy in reducing pain in low back pain patients. The method used in this study is a systematic review using narrative descriptive analysis. Search for research articles using databases from Science Direct, PubMed, and ProQuest, with a publication period of 2018-2023 (last 5 years). The six articles found in this systematic review show that all types of massage therapy interventions have an effect on pain in low back pain patients. Massage affects the muscular and skeletal systems in the superficial and deep layers to encourage healing and reduce pain. Conclusion: Massage therapy can be used to reduce pain in low back pain patients. Future researchers can use other complementary therapy interventions as a comparison to find out which complementary therapy interventions are more effective in reducing pain in low back pain patients.Keywords: Massage, Pain, Low Back Pain  ABSTRAK Low back pain adalah masalah umum yang disebabkan karena region lumbar menanggung sebagian besar berat badan. Nyeri dan disabilitas adalah salah satu masalah yang dapat ditimbulkan oleh low back pain yang berdampak pada kehidupan. Intervensi non farmakologis, seperti massage, akupuntur, manipulasi spinal, tai chi, dan yoga, direkomendasikan sebagai preferensi pengobatan pertama untuk low back pain. Systematic review ini bertujuan untuk mengetahui manfaat terapi massage dalam mengurangi nyeri pada pasien low back pain. Metode yang digunakan dalam penelitian ini adalah systematic review dengan menggunakan analisis deksriptif narasi. Pencarian artikel penelitian menggunakan database dari Science Direct, PubMed, dan ProQuest, dengan rentang waktu terbit 2018-2023. Keenam artikel yang ditemukan dalam systematic review ini menunjukkan bahwa semua jenis intervensi terapi massage memiliki pengaruh terhadap nyeri pada pasien low back pain. Massage mempengaruhi sistem otot dan kerangka di lapisan superfisial dan dalam untuk mendorong penyembuhan dan mengurangi rasa sakit Terapi massage dapat digunakan untuk mengurangi nyeri pada pasien low back pain. Peneliti selanjutnya dapat menggunakan intervensi terapi komplementer lain sebagai pembanding untuk mengetahui intervensi terapi komplementer yang lebih efektif digunakan dalam mengurangi nyeri pasien low back pain. Kata Kunci: Massage, Nyeri, Low Back Pain